O aparelho pré-ajustado: sua evolução e suas prescrições - Brito Júnior, Vicente De Sousa; Ursi, Weber José Da Silva [UNESP] (Dental Press Editora, 2006)
This research intended to review all the available prescriptions of pre-adjusted orthodontic appliances in the market and to discuss the justification of the authors as to the prescribed angulation, inclination and rotation suggested. The review encompassed the rectangular wire application in Edgewise brackets, until the implementation of self ligation, and many other kinds of brackets with distinct shapes according to the utilized technique. It was clear the great variety of many orthodontic mechanotherapy and brackets prescriptions, demonstrating that Orthodontics is a science with many possible alternatives.

Este trabalho revisou as prescrições de braquetes pré-ajustados existentes no mercado, abordando as variações dos valores de inclinação, angulação e rotação dentária. A revisão reporta desde a origem do conceito de uso de arcos retangulares em acessórios com secções retangulares até os atuais modelos de braquetes autoligados e outros braquetes com formatos diferenciados.
The pre-adjusted appliance: evolution and prescriptions
Keywords: Straight wire; Preadjusted appliances; Brackets prescriptions; Straight wire; Aparelho pré-ajustado; Prescrições de braquetes